What Methods Software Teams Prefer When Testing Web Accessibility - Aleksander Bai; Viktoria Stray; Heidi Mork (Advances in Human-Computer Interaction)
Accessibility has become an important focus in software development; the goal is to allow as many people as possible, regardless of their capabilities, to use software. We have investigated the methods that software teams prefer when testing the accessibility of their software. We conducted a large-scale study to evaluate six methods, using a sample of 53 people who work on various software teams. We present a detailed breakdown of the results for each testing method and analyze the differences between the methods. Our findings show that there are statistically significant differences in team members’ preferences, particularly for those with different roles. This implies that a software team should not choose a single method for all team members.